Green Synthesis of Fluorescent Ag Nanoclusters for Detecting Cu2+ Ions and Its “Switch-On” Sensing Application for GSH - Shang, Yunpeng; Gao, Hui; Li, Lei; Ma, Chaoqun; Gu, Jiao; Zhu, Chun; Yang, Zichen; Wang, Chengwei; Zhang, Ye; Chen, Guoqing (Journal of Spectroscopy, 2021)
Herein, we prepared the L-histidine- (His-) protected silver nanoclusters (Ag NCs) by the microwave synthesis method. The synthesis process was rapid, facile, and environmentally friendly. Under 356 nm excitation, the as-prepared Ag NCs exhibited the blue fluorescence, and the fluorescence emission peak was located at 440 nm. The Ag NCs could successfully detect trace copper (Cu2+) ions in the aqueous solution and the limit of detection (LOD) was as low as 0.6 pM. Interestingly, the Ag NCs showed a different pH-dependent selectivity for both Cu2+ and iron (Fe3+) ions with no responses to other heavy metal ions. Furthermore, the as-fabricated fluorescent sensing system was utilized to detect glutathione (GSH, the LOD was 0.8 nM) by using the “switch-on” fluorescence recovery of Ag NCs through adding glutathione (GSH) to the Cu2+-Ag NCs solution.